Pre-evaluation survey of Rohu G3 in Bangladesh: Highlyranked generation-three (G3) Rohu - Dam Lam, Rodolfo; Yeasin, Mohammed; Hamilton, Matthew; Rossignoli, Cristiano; Benzie, John (WorldFish, 2024)
The released of genetically improved ‘Generation 3’ or ‘G3’ rohu to several Bangladeshi hatcheries in 2020 was in the form of spawn. The hatcheries have subsequently grown this spawn into broodstock and commenced the production and sale of the genetically improved rohu seed in mid-2022 to nurseries. WorldFish track the dissemination of 48 of these nurseries (24 offering non-G3 rohu and 24 offering G3 rohu) from two Divisions (Khulna and Rajshahi). The nurseries have started to disseminate these G3 rohu to final customers starting from the last quarter of 2022 throughout the first half of 2023. This report aims to track this initial dissemination from nurseries to households in mid-2023 through a preevaluation survey.